SISTEM INFORMASI AKADEMIK BERBASIS WEB DI SMK NEGERI 1 SEMBORO - Hartono, Marga; Mumpuni, Indah Dwi; Setyowibowo, Sigit (DINAMIKA DOTCOM, 2014)
In this globalization era, a information can be spread rapidly, even just in a matter of second information can be accepted and delivered. A very useful information for all the people, and valueless moreover, in an institution and company.Through the information quickly and correctly to facilitate a lot of things wothy to gain information needed, for example businessman, the shops, enterpreneurs, restaurants, private education institutions as well as the country. Through the information quickly and correctly, exchange of information that will further develop and extends it.Because it, writer takes the theme about the information system based on the WEB. Academic with the existence of a web information can be packaged with such a way that information expressed can reach the target. In addition, the web potentially a good alternative and profitable for any storage medium information to the public at large.Â Key words : Â Academic Information Systems, Website